Camrelizumab-induced immune-related toxic epidermal necrolysis in lung adenocarcinoma: a case report and literature review - Sun, Man; Zhou, Huan; Zang, Dan; Liu, Chen-Guang; Chen, Jun (Frontiers in Oncology, 2025)
Toxic epidermal necrolysis (TEN) is a rare and serious skin reaction. This study reports a case of a patient with lung adenocarcinoma (LUAD) who developed severe TEN after 8 days of treatment with Camrelizumab monotherapy. The patient’s condition was effectively relieved with high-dose corticosteroids and intravenous immunoglobulin therapy. The diagnosis and treatment of immune-related TEN are challenging. This is a rare and severe case of TEN associated with the use of Camrelizumab. Additionally, we provide an in-depth understanding of immune-related TEN, summarizing its characteristics and treatment progress through a literature review, aiming to provide reference for the clinical safe application of immune checkpoint inhibitors (ICIs).